(3eQGbi GdeLO dBjGJ GdSYOs - (3CMeO Hf Ydj Hf YHO GdQMef GdefLhQ,J (B995 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje aGcJed MSf GdJCdja hLGA HMeO Gddg ef CHOY JUfja jSQ Hg ef jQhe GdJMbjb hjZjX ef MQe GdgOGjI hGdJhajb hSejJg eQGbi GdeLO dBjGJ GdSYO s
(3BNQgG (B:s
(3jfJgi GdehLhO efg CKfGA ShQI GdefGabjf Hbhdg hGfg SLd Ydjge HCfge cGPHhf ai bhdge Efc dQShd Gddg eY Cfg eWGHb ddhGbY adh cGf GdgOa YHGQI Yf eWGHbI GdhGbY deG UM gPG hQO gPG GdGSJOdGd HCf GdeYfi dcGPHhf ai GdTgGOI hGOYGFge s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi ghGeTgG JUMjMGJs
(3cJHJ GdYfGhjjf HGdMHQ GdCMeQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B10s
Keywords: (3Gdabg GdESdGejs